Serum vancomycin concentrations after oral and intracolonic vancomycin administration in a patient with colonic discontinuity and severe Clostridium difficile infection. (1st May 2018) - Wilke, Katja; Helbig, Sina; de With, Katja
Abstract : Purpose: A case of detectable systemic vancomycin levels after oral vancomycin administration but not after intracolonic administration in a patient with colonic discontinuity and severe Clostridium difficile infection (CDI) is reported. Summary: A 63-year-old woman who had recently undergone pancreas–kidney transplantation developed severe CDI after 13 days of meropenem therapy for presumed urosepsis. Meropenem was stopped immediately, and treatment with oral vancomycin (250 mg every 6 hours) was started. Due to fulminant C. difficile colitis with signs of toxic megacolon and abdominal compartment syndrome, an emergency left hemicolectomy (Hartmann's procedure) was performed. Ten days after initiation of oral vancomycin therapy, the serum vancomycin concentration was 16.7 mg/L. After oral dose reduction to 125 mg every 6 hours, the measured serum vancomycin concentrations stayed above 10 mg/L. CDI therapy was terminated after 16 days. Eight days later, as sigmoidoscopy of the Hartmann rectal stump still showed pseudomembranes, intracolonic vancomycin application in the Hartmann rectal stump was started; 7–9 days after initiation of intracolonic therapy, the serum vancomycin concentration remained undetectable. The observed patterns of vancomycin exposure and absorption in this case suggest that the sigmoid colon is not the site of resorption of intracolonically applied vancomycin. Conclusion: A patient with severe CDI and Hartmann rectal stump after hemicolectomy was treated with vancomycin. After oral vancomycin therapy, significant enteral absorption was observed, while levels stayed undetectable during intracolonic administration alone.